Effect of dietary water content on European sea bass (Dicentrarchus labrax) growth and disease resistance. Issue 2 (16th December 2014) - Przybyla, Cyrille; Fievet, Julie; Callier, Myriam; Blancheton, Jean-Paul
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of dietary water content on Dicentrarchus labrax growth parameters and resistance to Vibrio anguillarum infection was investigated using commercial pellets with identical energy contents and different moisture levels. The first experiment hypothesis was that moisturizing pelleted ration can have an impact on Dicentrarchus labrax growth performance by the osmoregulation energy cost reduction. In a second time, the experiment explores the effect of water addition in pellets on the fish resistance to a disease. A specific device was built to uniformly moisturize dry pellets to different moisture levels, i.e. 8%, 20%, 40% and 60%. After an acclimation period and a 54-day rearing period, the control fish had grown from 72.7 ± 17.9 g to 133.3 ± 29.4 g. No significant differences were recorded for fish growth parameters. After the growth period, the tagged fish were mixed and challenged by bath exposure to live Vibrio anguillarum in triplicate. After 7 days, mortality was significantly lower in the group of fish fed with pellets containing 60% water. Adding water to Dicentrarchus labrax feed did not affect fish growth parameters but increase its resistance to a Vibrio anguillarum infection. The moisturizing process could be used to add specific compounds (such as probiotics or vitamins) to pellets just before fish feeding and could have a positive effect on fish rearing.